Pectic polysaccharides as an acrylamide mitigation strategy – Competition between reducing sugars and sugar acids. (August 2018) - Passos, Cláudia P.; Ferreira, Sónia S.; Serôdio, António; Basil, Eva; Marková, Lucie; Kukurová, Kristína; Ciesarová, Zuzana; Coimbra, Manuel A.
Abstract: The main route for acrylamide formation is the reaction between reducing sugars and asparagine. As foods pH modulates acrylamide formation, cooking under the lowest pH is a possible mitigation strategy, as long as it does not compromise the expected foods sensorial characteristics. Polymeric acid compounds, such as pectin or pectate, which are acidic polysaccharides, can provide acidity without significant interference in taste or colour. To prove this hypothesis, biscuits were prepared with tartaric acid (control to acidic effect), and galacturonic acid in monomeric (GalA), oligomeric, and polymeric forms (pectin or pectate). While 1% GalA leads to 95% increase in acrylamide, biscuits prepared with 5% pectin had a 67% decrease. Replacing sucrose with fructose increased the acrylamide levels in control biscuits above the benchmark level of 150 μg/kg recommended by EFSA for children. However, addition of pectin/pectate had an effective acrylamide mitigation by lowering its content below these indicative values. Graphical abstract: Image Highlights: Pectin or pectate can act as acrylamide (AA) mitigation agents in cooked foods. Acidic polysaccharides lower biscuits dough's pH with consequent lower AA formation. Although reducing sugars promote AA formation, the acidity of pectate promotes its mitigation. Polysaccharide's addition does not affect biscuits taste and colour acceptability. This opens new opportunities for AA mitigation in fructose-rich formulations for diabetics.